(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Pregnancy is a wonderful moment as to give birth to new live. Physiological changes during pregnancy may lead to complication of both mother and baby. Among these preeclampsia, eclampsia and epilepsy are major cause of maternal mortality in developed and developing countries causing perinatal morbidity and mortality with foetal growth retardation. In Ayurveda, complications in pregnancy are not mentioned specifically. Masanumasik Paricharaya for Garbhini (regimen for the pregnant woman) is mentioned, which helps to prevent and cure disease and maintain health of mother and foetus. Pre-eclampsia and eclampsia mostly occurs after 20 weeks of gestation. During pregnancy mostly Madhura (sweet) Rasa drugs are used while in 6th and 7th month of pregnancy Acharya Sushruta has mentioned Gokshur and Pruthkparnyadi Gana additionally. Plants reviewed showed antiepileptic, anti-hypertensive, nootropic, anti-inflammatory, anti-oxidant, rejuvenative, diuretics, and cardio protective properties, which are helpful in safe and natural management of complications in pregnancy. So there is definite role of above drugs. Hence an attempt has been made to elaborate the role of these drugs in complications during pregnancy.